Evolution of food consumption patterns in upper middle-class Dhaka and how it shaped individuals and their relations to others - Rafa, Faiza Nuren (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2021.